2006
DOI: 10.1074/jbc.m603111200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Mitogen- and Stress-activated Kinase 1 by Arsenic Trioxide

Abstract: Arsenic trioxide (As2O3) is a potent inducer of apoptosis of leukemic cells in vitro and in vivo, but the precise mechanisms by which it mediates such effects are not well defined. We provide evidence that As2O3 induces activation of the mitogen- and stress-activated kinase 1 (MSK1) and downstream phosphorylation of its substrate, histone H3, in leukemia cell lines. Such activation requires upstream engagement of p38 MAPK, as demonstrated by experiments using pharmacological inhibitors of p38 or p38alpha knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 59 publications
(66 reference statements)
1
62
0
Order By: Relevance
“…An important role for mitogen-and stress-activated kinase 1 downstream of p38 in the regulation of ATO responses in leukemic cells was also proposed. 45 However, ATO-induced apoptosis in HepG 2 cells was shown to be independent of MAP kinase signaling pathways. 46 Consistent to Shim's report, 26 here we showed that ATO at 1 mM slightly activated p38 but not JNK, while bortezomib activated both JNK and p38.…”
Section: Discussionmentioning
confidence: 99%
“…An important role for mitogen-and stress-activated kinase 1 downstream of p38 in the regulation of ATO responses in leukemic cells was also proposed. 45 However, ATO-induced apoptosis in HepG 2 cells was shown to be independent of MAP kinase signaling pathways. 46 Consistent to Shim's report, 26 here we showed that ATO at 1 mM slightly activated p38 but not JNK, while bortezomib activated both JNK and p38.…”
Section: Discussionmentioning
confidence: 99%
“…One cascade involves activation of p70 S6K, which regulates phosphorylation of the S6 ribosomal protein and the initiation factor 4B (60 -66). The other mTOR-regulated cascade involves hierarchical phosphorylation of the translational repressor 4E-BP1 on Thr-37/46, Thr-70, and Ser-65, events that ultimately lead to its deactivation and dissociation from the eukaryotic initiation factor 4E, to allow cap-dependent translation (51)(52)(53)(54)(55)(56)(57)67). Activation of mTOR and its effectors is induced by various cytokines, hormones, and receptor tyrosine kinases, and such activation is important for the generation of mitogenic and cell proliferative responses (60 -66).…”
Section: Discussionmentioning
confidence: 99%
“…22,[24][25][26] Immunoblotting using an enhanced chemiluminescence (ECL) methodology was performed as in our previous studies. [24][25][26][27] In the experiments in which the pharmacologic inhibitors pepstatin A and E-64d were used, the cells were pretreated for 60 minutes with the indicated concentrations of the inhibitors before the addition of AS 2 O 3 to the cultures. siRNA-mediated knockdown of Beclin 1 or Atg7 in human leukemic cells was performed using Nucleofector kits from Amaxa Biosystems.…”
Section: Cell Lysis and Immunoblottingmentioning
confidence: 99%
“…The effects of AS 2 O 3 on leukemic progenitor colony formation were assessed by clonogenic assays in methylcellulose, as previously described. 22,24,25,27 Acridine orange staining and flow cytometric analysis Formation of acidic vesicular organelles (AVOs), a morphologic characteristic of autophagy was quantitated by acridine orange staining. 28 Acridine orange (0.5 mg/mL; Invitrogen) was added 15 minutes before collection and after washing with phosphate buffered saline, cells were analyzed by flow cytometry.…”
mentioning
confidence: 99%